WILLINGNESS TO PAY MASYARAKAT UNTUK MELINDUNGI TERUMBU KARANG DI PULAU WEH - Ikhsan, Ikhsan; Syahrival, Bilal (JURNAL KEBANGSAAN, 2014)
Coral reef ecosystems provide coastal populations with a number of goods and services, such as fisheries and tourism. They also form a unique natural ecosystem, with an important biodiversity value as well as scientific and educational value . Also, coral reefs form a natural protection against wave erosion. The aim of this study was to discover factors effecting the community to pay for their beneficial existence of coral reeef. The study was conducted by using cross section data on February 2013. Therefore, 152 respondents were selected by stratified random sampling and to them distributed the questionnaire to get the data. The Ordinary least Square (OLS) methode is used to estimate the partial model in this study. The estimation result shows that community income and organization member of environment have a positive and and significant effect on willingness to pay. Meanwhile education also has a positive impact on willingness to pay but this variable is not significant statistically. This caused by the size used in sample size. The limitation of this reseach is sample size. Appropriate sample size usually can eliminate the econometric problems in estimate result. Therefore, to obtain the best performance of this model it is needed further research using more sample size and more variable such as the number of family member.Keywords : Willingness to pay, coral reef, community